Overview of the Black Fungus Gnats from the Tristan da Cunha archipelago, including a redescription of Hyperlasion viridiventris (Frey) (Diptera: Sciaroidea: Sciaridae). - Menzel, Frank; Vilkamaa, Pekka; Smith, Jane E. (Contributions to Entomology = Beiträge zur Entomologie, 2013)
Black Fungus Gnats (Diptera: Sciaridae) were collected with Malaise traps on Tristan da Cunha and Nightingale islands in the South Atlantic. Four species were identified of which Lycoriella sativae (Johannsen, 1912) is already known from literature. For three others – Bradysia tilicola (Loew, 1850), Hyperlasion viridiventris (Frey, 1945) and Pseudolycoriella setigera (Hardy, 1960) – this is the first report from this archipelago. To date, 8 species are known from this group of islands. They belong to the genera Bradysia Winnertz (3 species), Cosmosciara Frey (1), Hyperlasion Schmitz (1), Lycoriella Frey (2) and Pseudolycoriella Menzel & Mohrig (1). The male genitalia for 7 particularly well known sciarid species from the archipelago are already illustrated but until now only poorly preserved type specimens of Hyperlasion viridiventris (Frey) from the Azores were known. Both male and female have been redescribed from the new material. An overview is also given of the existing sciarid records from the islands. The published data were analysed and compared with the new records.KeywordsDiptera, Sciaroidea, Sciaridae, Bradysia, Cosmosciara, Hyperlasion, Lycoriella, Pseudolycoriella, Afrotropical Region, South Atlantic, Tristan da Cunha archipelago, overview, distribution, redescription, new records.